“Child’s Own Voice”: Representing the Child Audience - Lynn Whitaker (University of Edinburgh, 2009)
This article, drawn from my doctoral research into children’s public service broadcasting (PSB) in the UK in the 21st century, examines the role that the child’s voice plays in the construction of the child audience made by producers of children’s television in their texts, production practices and discourse. It is argued that both the literal and figurative concept of the “child’s own voice” is a doctrine frequently deployed by producers to claim an authenticity or transparency to their representations. Through this doctrine, producers stress the relevance and appeal of representations of the child audience and thus foreground television’s probity as a beneficial cultural artefact under the aegis of public service broadcasting. By analysis of a specific case study, drawn from my role as participant-observer in the BBC Scotland Children’s department under the AHRC’s collaborative doctoral award scheme, I illustrate and discuss the key elements of the doctrine of child’s own voice that producers of public service children’s media frequently invoke.